The Effect Of Sawdust Addition To Physical Body Of Kidul Clay Based Earthware Ceramic - Sundari, Komang Nelly (Mudra Jurnal Seni Budaya, 2017)
The research on "The Effect of the addition of sawdust on the physical properties of ceramic body of Kidul clay-based Earthenware " has been performed with different percentages. The sawdust used is wood shavings waste ofbuilding materials. Based on the results ofehemical analysis, sawdust is known to have a tendency as a fuser, whereas Kidul clay contain enough clay substance / loam, feldspar and quartz minerals. This study aims to determine the physical properties of the composite body period, either in a state of pre-combustion and post-combustion as ceramics earthenware. The produced ceramic objects can be used as a container of crop water by permeation techniques. So what is sought is a composition with a value permeation / absorption ofwater / the greatest PA. To observe its physical properties, measures of laboratory scale study was conducted by testing the bricks and the scale of production through prototype test. The result is in accordance with the purpose that is the body mass of BG1 code that has been qualiï¬ed as Earthenware ceramics at a fuel temperature of l.l50oC with a value PA = 20.2% (SNI: 7275-2008, PA> 15% categorized as soft delicate earthenware or mayolika, while SII: 0803-83, PA> 20% is categorized as smooth soft earthenware with fuel temperature of l000oC). However, further research still needs to be done with the addition ofan adjuvant sawdust with varied percentages in addition to testing with various forms ofdesign in order that in terms of aestheties and function the earthenware ceramic objects later become more meaningful. Key words: Kidul clay, sawdust, earthenware, water absorption, shrinkage amount